Imposto sobre a renda e proventos de qualquer natureza da pessoa física: aspectos infra-constitucionais relevantes - Afonso, Sylvio César (2008)
The Tax Law is one of the most complex and fascinating branches of the Brazilian Law, and is certainly the most controversial and conflicting. This conflicting nature derives from the current incompatibility between the tax burden and the quality of the public utilities rendered, and also the continuous violation of the constitutional principles, causing a disagreement among the taxpayers. The purpose of this work is to confront the constitutional, legal and academic analysis, related to the systems of establishment, calculation and collection of the Individual Income Tax IRPF, with a practical analysis, meaning the specific way the taxpayer obtains the effective tax calculation basis and calculates the amount due. In this sense, the direction given by the constitutional provision is to focus on the balance of the conflicting relation between the Tax Administration and the taxpayers, and also the ethics on tax matters, imposing that the public interest respects the individual and collective rights and duties established by the Brazilian Federal Constitution. However, provided the existence of some conflicting practical issues of the taxation herein mentioned, this study intends to approach in more details a few current situations presenting incompatibility